The nurse in patient quality and safety (Research, Society and Development, 2021)
In nursing, patient care and safety has been a key factor since Florence Nightingale's time and many researchers believe that theories help to achieve better nursing outcomes. The objective of the research was to know the scientific evidence regarding the work processes that encompass patient safety and risk management. Methodological path of the Integrative Literature Review type, through the descriptive model, with a qualitative approach. For analysis, the "Thematic Content Analysis of Bardin" was used. For data collection, an instrument adapted from (URSI 2005) was used. For scientific search, articles referring to the period from 2016 to 2020 were selected, which had as descriptors: “Nursing”; "Quality management"; "Patient safety". The collections were searched in LILACS and SCIELO databases. The final sample consisted of 12 scientific articles, and the results were more concentrated in the SCIELO database with 7 articles, corresponding to 58%, and in LILACS with 5 articles, corresponding to 42% of the total sample. It was discussed how the work processes performed by nurses are performed and how their perception is important in thinking and making decisions. The daily relationships with members from other areas of expertise to pursue purposes through training, improvement cycles leads us to identify the social system in these activities, which in addition to a dynamic interaction, leads these professionals to work together for a common good: patient safety.